Perceived Harm and Addictiveness of e-Cigarette: A Systematic Review - Susi Ari Kristina; Ni Putu Ayu Linda Permitasari; Ahmad Intihan; Dima Nurrohmah Hayati; Kharisma Aprilita Rosyidah (Faculty of Pharmacy, Universitas Gadjah Mada)
The popularity of electronic nicotine delivery systems (ENDS), also known as e-cigarette, has been growing rapidly in the past years. Therefore, it is also important to explore how e-cigarette users perceive its harm and addiction risk. The aim of this study is to review and determine perceived harm and addictiveness of e-cigarette among e-cigarette users. We conducted a systematic review for published articles in English that had reported about perceived harm and addictiveness of e-cigarette published during year 2008 to 2018. Relevant studies were located through an extensive search from three electronic databases (PubMed, Science Direct, and Cochrane Database of Systematic Reviews) and Google Scholar on October 2018. Key terms used were “perceived harm”, “perceived risk”, “harm and addictiveness”, “belief”, “electronic cigarette”, “e-cigarette”, and “vaping”. A result of 88 studies were retrieved and reviewed. After further inspection of references from the collected studies, only 5 selected studies met all inclusion criteria. The final studies consisted of three cross-sectional studies, one longitudinal, and one prospective study. E-cigarette were perceived harmless and less addictive than cigarettes among its users with many predictors associated, including sex, age, race, education, advertisement and health belief for smoking cessation. Compared to non-users, e-cigarette users were significantly less likely to worry about the health risks, either its harm or addictiveness. E-cigarette was perceived harmless and less addictive than tobacco cigarettes. Further study about e-cigarette profile is particularly important to design public health messages that accurately interpret the scientific data on the potential harm and addictiveness of e-cigarette.